Middle Black Sea Region Fishing and Socioeconomic Status of Fishermen - Yucel, Sennan (Ege University, 2006)
It is an expected result that in agricultural output when proportion of plantal production decreases, proportion of aquatic production increases during industrialization. However it can not be said that Turkey provides this transformation. In order to investigate the last ten year of fisheries and aquaculture sector, indexes were prepared accepting the year of 1994 as basic circuit. As a result of statistical analyses, increase of freshwater fisheries and culture among the production categories and fishing vessel of 5-9.9 m according to the length of vessel were found to be significant (p<0.05). The qualification of product is as important as quantity of product in sustainable production. The focal-point of activation in presenting of qualified product is formed by fishermen. 51% of fishermen of Middle Black sea region were at the age of 30 to 50 and just 1% of them was graduated from high school. % 6% of fisherman had no social security, 34% of them were doing the fishing as second job and 54% of them had an obligation of looking after 5 and more person. As a results, People should be trained as required quality of aquaculture and fisheries economy in the direction of sectoral necessity.
Yücel, Sennan/0000-0002-0522-9846;
Keywords: Fishermen; Fisheries; Socio-Economical Position; Partner Life; Middle Black Sea